Design And Development Of Semiconductor Based And Fiber Laser Based Optical Transmitter - Arsad, Norhana (2003)
This thesis presents the research works on development, characterization, application and analysis of semiconductor based and fiber laser based optical transmitter. Semiconductor laser is the most widely used in the optical communication system. This is mainly because of the compact size, weight and simplicity of modulation scheme. Laser diode is used in developing the optical transmitter and the application in the optical communication. The function of the optical transmitter is to convert the electric signal into optical signal and thus the optical transmitter is also called Electric to optical (E/O) converter. There are two approaches used in this thesis : simulation and experiment. Simulation is designed to check and determine the functionality of the designed circuit.